2017
DOI: 10.1177/1535370216685007
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B X-interacting protein promotes cisplatin resistance and regulates CD147 via Sp1 in ovarian cancer

Abstract: We found that hepatitis B X-interacting protein (HBXIP) was able to activate the CD147 promoter through Sp1. In vivo, depletion of HBXIP decreased the tumor volume and weight induced by CP. Taken together, these results indicate that HBXIP promotes cisplatin resistance and regulated CD147 via Sp1 in ovarian cancer cell lines. AbstractOvarian cancer is the highest mortality rate of all female reproductive malignancies. Drug resistance is a major cause of treatment failure in malignant tumors. Hepatitis B X-inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
0
5
0
1
Order By: Relevance
“…Interestingly, in addition to being the downstream substrate of caspase-3, Bcl-2, with its antiapoptotic property, can be inactivated by caspase-3 and converted into a pro-apoptosis motivator unrelated to Bax/Bcl-2 pathway, suggesting that a feedback loop between Bcl-2 and caspase-3 exists [ 156 ]. Considerable evidence supports the idea that enhanced Bax/Bcl-2 ratio, combined with cleavage of caspase-3, takes place in various liver diseases, including chronic hepatitis, alcoholic liver, and hepatocellular carcinoma (HCC) [ 157 , 158 , 159 ].…”
Section: Network Pharmacology-associated Studymentioning
confidence: 99%
“…Interestingly, in addition to being the downstream substrate of caspase-3, Bcl-2, with its antiapoptotic property, can be inactivated by caspase-3 and converted into a pro-apoptosis motivator unrelated to Bax/Bcl-2 pathway, suggesting that a feedback loop between Bcl-2 and caspase-3 exists [ 156 ]. Considerable evidence supports the idea that enhanced Bax/Bcl-2 ratio, combined with cleavage of caspase-3, takes place in various liver diseases, including chronic hepatitis, alcoholic liver, and hepatocellular carcinoma (HCC) [ 157 , 158 , 159 ].…”
Section: Network Pharmacology-associated Studymentioning
confidence: 99%
“…In recent years, important progress on the regulation of beta receptors in different pathological processes has been reported. For example, a study on beta-arrestin1 knockout mice revealed that under chronic stress, DNA damage and genomic instability resulted from the β-AR-beta-arrestin1 pathway ( 12 ). Our study found that CD147 was up-regulated by β-AR under NE stimulation, but no obvious increase in MCT1 and MCT4 was observed, this result is not shown in the article.…”
Section: Discussionmentioning
confidence: 99%
“…CD147 (also known as extracellular matrix metalloproteinase inducer, EMMPRIN) is widely expressed on the surface of a variety of tumor cells (10,11). Importantly, CD147 can stimulate fibroblasts to produce diverse matrix metalloproteinases (MMPs) (12,13). But it also can stimulate tumor cells to produce MMPs, specifically MMP-2 and MMP-9.…”
Section: Introductionmentioning
confidence: 99%
“…GeneMANIA results indicated that MMP1 was closely associated with 20 genes, including BSG, TRIP6, ITGA2, F2R, MMP3, COPS5, etc. And four genes (ITGA2, BSG, TRIP6, and COPS5) have been found to regulate drug resistance in different cancer models [ 56 59 ]. Especially, COPS5 was significantly upregulated in the erlotinib resistance dataset GSE80344 and NSCLC tissues.…”
Section: Discussionmentioning
confidence: 99%